New cardo bisphenol monomer containing pendant azido group and the resulting aromatic polyesters - Maher, Deepak M.; Nagane, Samadhan S.; Jadhav, Uday A.; Salunkhe, Pravin H.; Tawade, Bhausaheb V.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2019)
Expanding on our strategy to synthesize aromatic step-growth polymers containing pendant clickable azido groups via functional monomer approach, we have now designed and synthesized a new cardo bisphenol, viz., 2-(2-azidoethyl)-3, 3-bis(4-hydroxyphenyl) isoindolin-1-one (PPH-N-3). PPH-N-3 was conveniently synthesized starting from commercially available phenolphthalein by a three-step route in an overall yield of 65% using simple organic transformations. Aromatic (co)polyesters bearing pendant azido groups were synthesized by low-temperature solution polycondensation of PPH-N-3 or different molar ratios of PPH-N-3 and bisphenol-A (BPA) with aromatic diacid chlorides in dry dichloromethane in the presence of triethylamine (TEA) as a base. The formation of medium to reasonably high-molecular-weight (co)polyesters was evidenced from intrinsic viscosity and number-average molecular-weight measurements that were in the range 0.52-0.85 dL/g and 16,700-28,200, respectively. Tough, transparent, and flexible films could be cast from chloroform solutions of these (co)polyesters. (Co)polyesters were characterized using FTIR, H-1 NMR, C-13 NMR spectroscopy, XRD, and TGA. The thermal curing reaction of (co)polyesters involving decomposition of azido groups was studied by DSC analysis. The chemical modification of a representative copolyester containing pendant azido groups was carried out quantitatively using catalyst-free azide-maleimide cycloaddition reaction with two maleimides, namely, N-methylmaleimide and N-hexylmaleimide. (c) 2019 Wiley Periodicals, Inc.
Keywords: aromatic (co)polyester; azido group; cardo bisphenol; Chemical modification

Synthesis of novel of 2, 5-disubstituted 1, 3, 4-oxadiazole derivatives and their in vitro anti-inflammatory, anti-oxidant evaluation, and molecular docking study - Kashid, Bharat B.; Salunkhe, Pravin H.; Dongare, Balasaheb B.; More, Kishor R.; Khedkar, Vijay M.; Ghanwat, Anil A. (Bioorganic & Medicinal Chemistry Letters, 2020)
A series of novel 2, 5-disubstituted 1, 3, 4-Oxadiazole derivatives as a potential anti-inflammatory, and antioxidant agent were synthesized via cyclisation. Hydrazide molecule treated with substituted acids in the presence of phosphorus oxychloride (POCl3) as an efficient reagent as well as solvent by conventional method with shorter reaction time and excellent yield. The newly synthesized 1, 3, 4-oxadiazole derivatives exhibited excellent to good anti-inflammatory and anti-oxidant activities compaired to the standard drugs. Molecular docking study on the crucial anti-inflammatory target-cyclooxygenase-2 (COX-2) revealed the ability of the scaffold to correctly recognize the active site and achieve significant bonded and non-bonded interactions with key residues therein. This study could identify potential compounds which can be pertinent starting points for structure-based drug design to obtain newer anti-inflammatory agents.
Keywords: 1; 3; 4-Oxadiazole; Anti-inflammatory; Anti-Oxidant; Biological activity; computational chemistry